Implementasi Penilaian Berbasis High Order Thinking Skills dalam Meningkatkan Kemampuan Berpikir Kritis dan Kreatif pada Mata Pelajaran PAI dan Budi Pekerti (QUALITY, 2021)
AbstractThis study aims to analyze the concept of HOTS based assessment to improve students critical and creative thinking skills, the implementation of HOTS based assessments in improving students critical and creative thinking skills, results of HOTS-based assessments in improving students abilities. critical and creative thinking of students in the subjects of Islamic Religious Education and Character Education at the Junior High School level in Kudus Regency. This type of research uses descriptive qualitative. Data collection techniques using observation, interviews, and documentation. Data analysis techniques using Milles and Huberman analysis models include data reduction, data presentation, drawing conclusions. Results of this study indicate that the HOTS based assessment concept consists of analyzing the Basic Competencies; compiling a grid of questions; choosing a stimulus; write question items; and make scoring guidelines. Implementation of the HOTS based assessment consists of the dominance of the cognitive aspect in making questions; cognitive level creates, evaluates and analyzes as a reference in making questions; and making questions oriented towards measuring the metacognitive dimensions of students. Results of the HOTS based assessment can be seen from the mastery of the material with a higher level, and the ability to think systematically, learn to analyze a problem from various aspects and educate students to be confident. Thus, HOTS based assessment is important to be implemented in learning activities, with the aim that students are able to think creatively, critically, innovatively, argue, solve problems, and have expertise in making decisions, especially on Islamic Religious Education and Character Education materials.AbstrakPenelitian ini bertujuan untuk menganalisis konsep penilaian berbasis HOTS untuk meningkatkan kemampuan berpikir kritis dan kreatif peserta didik, implementasi penilaian berbasis HOTS dalam meningkatkan kemampuan berpikir kritis dan kreatif peserta didik, dan hasil penilaian berbasis HOTS dalam meningkatkan kemampuan berpikir kritis dan kreatif peserta didik pada mata pelajaran PAI dan Budi Pekerti di tingkat SMP Kabupaten Kudus. Jenis penelitian ini menggunakan kualitatif deskriptif. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan model analisis Milles dan Huberman meliputi reduksi data, penyajian data, menarik kesimpulan. Hasil penelitian ini menunjukkan bahwa konsep penilaian berbasis HOTS terdiri dari menganalisis KD; menyusun kisi-kisi soal; memilih stimulus; menulis butir pertanyaan; dan membuat pedoman penskoran. Implementasi penilaian berbasis HOTS terdiri dari dominasi aspek kognitif dalam membuat soal; level kognitif mencipta, mengevaluasi dan menganalisis menjadi rujukan dalam membuat soal; dan pembuatan soal berorientasi mengukur dimensi metakognitif peserta didik. Hasil penilaian berbasis HOTS terlihat dari penguasaan materi dengan level yang lebih tinggi, dan kemampuan berpikir secara sistematis, belajar menganalisis suatu masalah dari berbagai aspek dan mendidik peserta didik percaya diri. Dengan demikian penilaian berbasis HOTS penting untuk diimplementasikan dalam kegiatan pembelajaran, dengan tujuan agar peserta didik mampu berpikir kreatif, kritis, inovatif, berargumen, menyelesaikan masalah, dan keahlian dalam mengambil keputusan, khususnya pada materi PAI dan Budi Pekerti.